The positive role of parents and family in home-based literacy: An Integrative Review - Tiyas Abror Huda; Een Yayah Haenilah (Indonesian Journal of Innovation Multidisipliner Research, 2024)
This study analyzes and explores home-based literacy based on prior research indexed by Scopus and published between 2020 and 2022 to determine the roles parents and families play in learning home-based literacy. The analysis was explicitly done in the area of education. Search outcomes for article samples were discovered using a Scopus.com account. The author used the integrated review methodology and looked up to 12 papers. The author concludes that when parents and families participate, home-based literacy programs greatly benefit children's learning and development. Parents and families must support children's literacy development through reading books, labelling objects, telling stories, teaching numbers and letters, and reciting nursery rhymes. The activity's success is also influenced by the parent's educational attainment and financial standing in carrying out their duties. The more educated and wealthy a person is, the simpler it will be to implement at-home literacy initiatives. Conversely, implementation will be hampered by the parents' lower levels of education and wealth. However, this can be avoided by connected parties cooperating, specifically by providing children and parents with access to free books at home.